Seaweed minerals as nutraceuticals - Mišurcová, Ladislava; Machů, Ludmila; Orsavová, Jana (Advances in food and nutrition research, 2011)
Seaweed is known as an abundant source of minerals. Mineral composition of seaweed is very changeable because of many exogenous and endogenous factors and differs also within the same species. Principally, seaweed is an excellent source of some essential elements. Mainly, iron and iodine are in high concentration. Seaweeds could be prospective as functional foods and also producers of mineral nutraceuticals.
Keywords: mořské řasy; potravní doplňky; minerály; Nutritional Physiological Phenomena; fyziologie výživy; Humans; Seaweed; lidé; Minerals; Dietary Supplements; biologická dostupnost; Biological Availability